Capacitismo no contexto escolar: entre preconceito estrutural e perspectivas emancipátorias - Mapurunga, Francisco Alexandre Dourado (2024)
This research explores the theme of ableism in inclusive education, related to individuals with disabilities and their right to access and learn in mainstream schools. The term ableism comes from disability studies to designate prejudice and structural oppression against people with disabilities, while inclusive education is the emancipatory perspective of special education that views mainstream schools as democratic spaces for educating everyone without excluding anyone based on their disability. Thus, this study aims to analyze ableism in the educational context from the perspective of various community actors - teachers, administrators, families, individuals with disabilities, and social movements. The specific objectives are: i) to map the genesis of the concept of ableism in Brazil; and ii) to identify manifestations of ableism in educational practices in the context of public regular schools, from the perspective of the participants of this investigation. The theoretical foundation of this research can be divided into two main axes that dialogue and complement each other as conceptual references: Special Education from the perspective of Inclusive Education (Lustosa, 2009; 2021; 2023; Mantoan, 2006; Figueiredo, 2010; 2013); and Disability Studies and Ableism (Mello, 2009; 2012; 2014; Gesser, Block, and Mello, 2020; Gáverio, 2017; Diniz, 2012; Dias, 2013), Bardin (1970; 1977); Bogdan & Biklen (2019) in the methodological approach. The methodology adopted is qualitative collaborative research, guided by the Freirean Model of Emancipatory Disability Research, proposed by Deepak (2019). The empirical data were collected in four reflective workshops and analyzed using Content Analysis (Bardin, 1977). The subjects of this research are actors in the school community who live with the perspective of inclusive education: inclusion activists (OPD), people with disabilities and their families, special education teachers, regular classroom teachers, and administrators, engaged as co-researchers who contributed with their narratives and shared experiences and knowledge. The results of this research show that Disability Studies and Crip Theory coined the term ableism in Brazil, emerging as a neologism, a translation of the English word "ableism," also adopted in other Spanish- and Portuguese- speaking countries. The research argues that for there to be educational inclusion and the dismantling of ableism, it is necessary to adopt the social model of disability, a conception that recognizes disability as an expression of human diversity, rather than a diminished state of being. The information produced also indicates that ableism erodes and corrupts the very notion of inclusion, infiltrating individualistic and charitable conceptions and distorting the perception of inherent dignity of people with disabilities. It concludes that inclusion, as a movement that installs itself in the school context, is traversed by processes of resistance and denial that can be attributed to ableism. While it has the power to eliminate discriminatory and exclusionary practices, inclusion can be undermined by the very structure that generates exclusion and attempts to end it, sometimes explicitly, other times subversively.